MONITORING ARUS DAN TEGANGAN PEMBANGKIT LISTRIK TENAGA SURYA BERBASIS INTERNET OF THING DI ASONE HIDROPONIK - Zidane, Imam Rafi; Abdurrahman; Alfarizal, Niksen (JURNAL TELISKA, 2025)
Hydroponics is a farm method that does not use soil as the growning medium. But instead utilizes water mixed with nutrients required by the plants. This method is considered more efficient in limited city land and allows for full control over nutrient provided to the plants. The utilization of Solar Power Plant is the best solution to solve the problem of PLN power outage, particulary in supporting irrigation and nutrient supply for hydroponic plant cultivation. This research is focus on developing a monitoring system for the current and voltage generated by the Solar Power Plant to ensure a stable and efficient power supply. The system is designed based on the Internet of Thing (IoT) enabling Asone Hydroponic cultivators to perform real time monitoring via Blynk app on both Android and PC. The objective of this research is to design and create a Solar Power Plant monitoring system that can measure and monitor voltage and current variables and to implement it in the context of hydroponics plant cultivation. Using the ESP32 as a microcontroller, this research also use the PZEM-017 sensor to measure DC voltage and current, and the PZEM-004t sensor to measure AC voltage and current. It is hoped that this research will provide tangible benefits in improving the efficiency and sustainabillity of hydroponic plant cultivation in Indonesia, as well as offer a reliable renewable energy solutions.